2014
DOI: 10.1089/ars.2013.5417
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Translocation of p53 Modulates Neuronal Fate by Preventing Differentiation-Induced Mitochondrial Stress

Abstract: In conclusion, our results reveal a novel role for mitochondrial p53, which modulates mitochondrial damage and apoptosis-related events in the context of neural differentiation, thus enhancing neuronal fate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 68 publications
4
46
0
Order By: Relevance
“…Interestingly, they reported that after growth factor depletion mROS reached a maximum increase of ~200% at 1 h and this increase was significantly but not completely restored at 3 h (no further time points were tested) [24]. Results from Xavier and colleagues are in agreement with our findings, also reporting a transient increase in superoxide mROS 1 h after the induction of NSC differentiation [27]. These results are in line with ours when using 60 sec of laser, indicating that 405 nm laser exposure is capable of triggering processes similar to those occurring at early stages of NSC differentiation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, they reported that after growth factor depletion mROS reached a maximum increase of ~200% at 1 h and this increase was significantly but not completely restored at 3 h (no further time points were tested) [24]. Results from Xavier and colleagues are in agreement with our findings, also reporting a transient increase in superoxide mROS 1 h after the induction of NSC differentiation [27]. These results are in line with ours when using 60 sec of laser, indicating that 405 nm laser exposure is capable of triggering processes similar to those occurring at early stages of NSC differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated the mechanisms by which blue light has neurogenic properties in vitro. One single laser pulse of 60 sec (300 mW/cm 2 , 18 J/cm 2 fluence) transiently induces the generation of mitochondrial Nox-derived ROS to levels similar to those found during earlier stages of neuronal differentiation [24,27]. Hence, when finely tuned, light is capable of triggering ROS-involved physiological processes such as neuronal differentiation.…”
Section: Discussionmentioning
confidence: 83%
“…15 TUDCA prevented mitochondrial membrane depolarization occurring at early stages of neural differentiation, such as at 6 h, as assessed by a significant increase in DiOC 6 (3) mitochondrial incorporation (P < 0.01) (Fig. 1A).…”
Section: Tudca Prevents Differentiation-induced Mitochondrial Stressmentioning
confidence: 85%
“…15 In addition, we have previously demonstrated that TUDCA is a strong inhibitor of apoptosis by preventing mitochondrial apoptotic signaling, including mitochondrial membrane perturbations and cytochrome c release. 4,25 Therefore, we investigated the potential effect of TUDCA during differentiation-induced mitochondrial stress, as well as its efficacy in regulating NSC differentiation.…”
Section: Tudca Prevents Differentiation-induced Mitochondrial Stressmentioning
confidence: 99%
See 1 more Smart Citation